A pedagogia histórico-crítica e a formação da individualidade para sí - Duarte, Newton [UNESP] (My University, 2013)
Is there a place inside Marxism for the debate on individuality? Does the historical-critical pedagogy need a theory of individual’s education? The article answers affirmatively to both questions and analyses the pillars of a Marxist theory of human individuals’ education. The start point is the relation between the processes of objectification and appropriation that were originated by the work activity. The relation between objectification and appropriation is analysed from a dialectical materialistic historical perspective. This perspective implies the understanding of the contradiction generates by class struggle that gives to the sociocultural development both the meanings of humanization and alienation. In this sense, individual’s education is understood as part of historical self-building process of humankind. The direction of this movement is from humanity in itself to humanity for itself that means a process that promotes the development of free and universal individuality.

Hay espacio para debate en el marxismo sobre la individualidad? La pedagogía histórico-crítico necesita una teoría de la formación del individuo? El artículo responde sí a estas dos preguntas y analiza los pilares de una teoría marxista de la formación de la persona humana. El punto de partida es la relación entre los procesos de objetivación y apropiación que tienen su origen en la actividad laboral. Esta relación se examina desde una perspectiva dialéctica, materialista y histórica, con la comprensión de la contradicción generada por la lucha de clases que confiere al desarrollo socio-cultural tanto el significado de la humanización como de la alienación. Por lo tanto, la formación del individuo se entiende dentro del proceso histórico de auto construcción del genero humano, en un movimiento que parte del en sí y camina hacia el para si, es decir, que promueve la formación de la individualidad libre y universal.

Há lugar no marxismo para a discussão sobre a individualidade? A pedagogia histórico-crítica precisa de uma teoria da formação do indivíduo? O artigo responde afirmativamente a essas duas perguntas e analisa os pilares de uma teoria marxista da formação do indivíduo humano. O ponto de partida é a relação entre os processos de objetivação e apropriação que têm sua gênese na atividade de trabalho. Essa relação é analisada numa perspectiva dialética, materialista e histórica, compreendendo-se a contradição gerada pela luta de classes que confere ao desenvolvimento sociocultural tanto o significado de humanização quanto o de alienação. Dessa maneira, a formação do indivíduo é entendida no interior do processo histórico de autoconstrução do gênero humano, num movimento que parte do em si e caminha em direção ao para si, ou seja, que promove a formação da individualidade livre e universal.
The historical critical pedagogy and the education of the individuality for itself
La pedagogia histórico-crítica e la formación de la individualidad para sí
Keywords: Historical critical pedagogy; Individual’s education; Marxism; Pedagogía histórico-crítica; Formación del indivíduo; Marxismo; Pedagogia histórico-crítica; Formação do indivíduo; Marxismo